2013
DOI: 10.3389/fpls.2013.00431
|View full text |Cite
|
Sign up to set email alerts
|

The importance of aboveground–belowground interactions on the evolution and maintenance of variation in plant defense traits

Abstract: Over the past two decades a growing body of empirical research has shown that many ecological processes are mediated by a complex array of indirect interactions occurring between rhizosphere-inhabiting organisms and those found on aboveground plant parts. Aboveground–belowground studies have thus far focused on elucidating processes and underlying mechanisms that mediate the behavior and performance of invertebrates in opposite ecosystem compartments. Less is known about genetic variation in plant traits such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 162 publications
(250 reference statements)
0
23
0
Order By: Relevance
“…It has been hypothesized that when plant roots are exposed to belowground pathogens, defense responses are sent via a series of signaling molecules to the aboveground foliar. This has been demonstrated in several studies where responses triggered belowground were transported aboveground and vice versa to better prepare the plant for defense strategies . In oil palms, it has been shown that expression of defense‐related genes can be detected in both root and leaf tissues of Ganoderma ‐infected seedlings .…”
Section: Introductionmentioning
confidence: 88%
“…It has been hypothesized that when plant roots are exposed to belowground pathogens, defense responses are sent via a series of signaling molecules to the aboveground foliar. This has been demonstrated in several studies where responses triggered belowground were transported aboveground and vice versa to better prepare the plant for defense strategies . In oil palms, it has been shown that expression of defense‐related genes can be detected in both root and leaf tissues of Ganoderma ‐infected seedlings .…”
Section: Introductionmentioning
confidence: 88%
“…In their natural environment, plants engage in interactions not only above but also belowground. Moreover, indirect interactions between soil‐borne and aerial organisms may be mediated by the plant itself (van Dam & Heil, ; van Geem et al., ). In the context of these plant‐mediated interactions across spatial scales, LC‐MS based metabolic fingerprinting, alongside targeted glucosinolate profiling and GC‐MS based quantitation of primary metabolites, was used to detect chemical changes in local and systemic tissues of A. thaliana plants infested by aphids (leaves), nematodes (roots), or both (Kutyniok & Müller, ).…”
Section: Plant‐mediated Belowground–aboveground Interactionsmentioning
confidence: 99%
“…However, a recent study in cotton showed that root herbivory by the gall‐forming root‐knot nematode M. incognita had no impact on the performance of the cotton herbivore H. zea , which ultimately had no effect on the attraction of the parasitoid Microplitis croceipes (Cresson) to their hosts (Olson et al ., ). Therefore, we are only beginning to scratch the surface in our understanding of above‐ and below‐ground interactions between herbivores and their natural enemies (van Geem et al ., ; van Veen, ).…”
Section: Introductionmentioning
confidence: 97%